Challenges Facing the Conservation of Historic Buildings Through Local Eyes: The Swahili Town of Kilwa Kivinje, Tanzania. (2nd September 2018) - Lwoga, Noel Biseko; Mwitondi, Musa Said
ABSTRACT: This study explores the state of conservation of historic buildings and the challenges facing their conservation from the perspective of resident in Kilwa Kivinje in Tanzania. The findings based on observation of 34 buildings indicate that the majority are in a relatively poor state. Ethnographic inquiry with 22 residents indicates that this situation is due to not only a limited awareness of conservation issues and responsibilities, but also socio-psychological and relational challenges such as a limited sense of heritage ownership, the lack of interest and motivation to conserve, neglect by owners and occupants and lack of trust in the conservation authorities; and socio-economic challenges such as limited economic benefits and scarcity of resources. Residents also perceive that there is weak enforcement of antiquities legislation, limited assistance from the antiquities' agencies and that they are not involved in the decision-making process. Unlike past research that engaged in the authoritative discourse to explain the challenges of conserving heritage, this study has engaged in the under-researched resident discourse. It thus broadens our understanding of the challenges and further enlightens experts on the significance of considering residents' perspectives when designing and implementing conservation strategies. It also makes broad locally-based practical recommendations to cultural heritage management in Kilwa Kivinje and related sites in order to rectify the situation of poor state of conservation.